Tepung Fermentasi Kedelai Sebagai Pengganti Tepung Ikan dalam Pakan Buatan Terhadap Pertumbuhan Udang Windu (Penaeus monodon Fabricius) - Pinandoyo, Pinandoyo; Susilowati, Titik; Herawati, Vivi Endar; Budiati, Heri (Jurusan Perikanan dan Kelautan, 2014)
Growth and survival rate of shrimp affected by feed and water quality factor. Artificial diets is one alternative to improve the growth and survival rate of tiger shrimp. The study aims to determine the effect of substitution of the use of fish Flour with fermented soy flour againts growth and survival rate of tiger shrimp and determine the best treatment that can enhance growth and survival of shrimp. This research used experimental methode with completely randomized design with 4 treatments and 3 replications. The results showed that feeding treatment with different compositions will provide significant effect (P <0.05) on the growth and influence of absolute biomass are significantly different (P <0.01) the daily growth rate, but not significantly different at survival. Absolute biomass growth on treatment B hasi best provide for (2422.33 mg) and a row followed by treatment C (2225.87 mg), A (2108.07 mg) and D (1348 mg). The best daily growth were treatment B (8.15% / day), C (7.91% / day), A (7.82% / day) and D (6.64% / day). Percentage survival of C (72%), B (70%), D (69.33%) and A (64.67%). The results of measurements of water quality parameters as maintenance medium for research is still in a decent range for maintenance of tiger shrimp.